NUMERICAL TAXONOMIC STUDY OF SELECTED PLANTS OF ASTERACEAE FAMILY FROM AHMEDABAD DISTRICT, GUJARAT (International Association of Biologicals and Computational Digest, 2022)
The article is about the systematic study of 30 species that belongs to 26 genera of Asteraceae family in Ahmedabad District. A total of 52 characters were measured, comprising qualitative and quantitative characters. Characters and character states were determined through examination of both living and herbarium specimens. Numerical taxonomy, also termed as morphometric deals with grouping by numerical methods of taxonomic units into taxa on the basis of their character state. On the basis of UPGMA (Unpaired Group Method off Averaging) clustering, Neighbour joining cluster analysis and a dendrogram was constructed as two clades and other sub clade are recognized. Results obtained from the present study are found congruent with morphological studies showing the significance of numerical analysis for taxonomic relationship in the Asteraceae family
Keywords: Systematic study, Asteraceae, numerical analysis, Numerical taxonomy morphological characters, Dendrogram, clade, taxonomic relationship